2019
DOI: 10.1186/s40900-019-0164-0
|View full text |Cite
|
Sign up to set email alerts
|

How helpful are Patient and Public Involvement strategic documents - Results of a framework analysis using 4Pi National Involvement Standards

Abstract: BackgroundPatient and Public Involvement (PPI) strategic documents are viewed as an essential feature of organisational commitment to openness and transparency. They provide a mechanism to communicate opportunities for wider community influence in healthcare. The absence of documentation can be negatively interpreted, for example during regulatory inspection, as a lack of intent by organisations to collaborate with a broad constituency. Published literature paints a confusing picture of rationale and evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Members of the public include a wide range of people including: patients, potential patients, family carers, service users, people using health and social care services as well as people from organisations that represent people who use services [9]. To support this growing area of research, a range of patient and public involvement (PPI) guidelines, frameworks and standards have been developed for researchers and PPI contributors alike [9][10][11][12][13]. In the UK, National Standards for Public Involvement were launched in 2018 and updated in November 2019 to "improve the quality and consistency of public involvement in research" [14] .…”
Section: Introductionmentioning
confidence: 99%
“…Members of the public include a wide range of people including: patients, potential patients, family carers, service users, people using health and social care services as well as people from organisations that represent people who use services [9]. To support this growing area of research, a range of patient and public involvement (PPI) guidelines, frameworks and standards have been developed for researchers and PPI contributors alike [9][10][11][12][13]. In the UK, National Standards for Public Involvement were launched in 2018 and updated in November 2019 to "improve the quality and consistency of public involvement in research" [14] .…”
Section: Introductionmentioning
confidence: 99%
“…This, in turn, would more sharply demarcate the claims of PPI while locating its status within organisations and the wider world of volunteering. Such a discursive resolution is apparently sought and certainly needed, given the constantly expressed regrets about lack of agreement or shared understanding among PPI interest groups, about what PPI is and should be 9,10 …”
Section: Discussionmentioning
confidence: 99%
“…PPI in health research and service decision‐making is commonly described as ‘imperative’ for improving patient experiences 8 . However, following decades of implementing PPI, a marked lack of agreement or even shared understanding of what it is and should be persists among those interested in PPI or even those involved in it 9 . A repeated criticism of PPI is its being conducted as little more than a ‘tick box exercise’ 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Matthews et al reported that documents intended for the public are often not written with the public [ 29 ]. PPI provides the opportunity for the public to have their say and to be viewed by a “fresh-eyed reviewer” [ 30 ], influencing health care to their bespoke needs.…”
Section: Main Bodymentioning
confidence: 99%